An Analysis of Factors Related to the Ability of Hypoglycemic and Hyperglycemic Early Detection in patients of Diabetes Mellitus in Bima Public Hospital in 2017 - Martiningsih Martiningsih (Media Keperawatan Indonesia, 2018)
This study aims to determine the ability of early detection, the factors that are most influential and related to the ability of early detection of hypoglycemia and hyperglycemia in diabetes mellitus patients in Bima Public Hospital in 2017. The method used in this research is an analytical descriptive method and uses a cross-sectional approach. The population of this study was all DM patients in Bima Public Hospital in 2017. The sample size was determined by purposive sampling technique, namely 30 people. The study was conducted in the internal medicine room of Bima Hospital. The data were retrieved by using questionnaire of Ability to Detect Hypoglycemia and Hyperglycemia which has been tested for the validity and reliability of the instrument with Cronbach's Alpha value of 0.734. The data analysis process was carried out by using Chi-Square test and logistic regression. Results: The ability of hypoglycemia and hyperglycemia to be detected in DM patients in Bima Public Hospital in 2017 was 47% who were able and 58% who were not able with the average of 42.70, with a minimum-maximum value of 34-52. The results of the multivariate test revealed that the duration of DM disease had the most significant effect on the ability of hypoglycemia and hyperglycemia detection (p-value = 0.001, OR 39.429). Discussion: Improving the quality of nursing care through self-care education in the right nursing perspective with regard to the characteristics of the respondents, one of them is a history of long-term DM disease, can prevent acute hypoglycemia and hyperglycemia.